2021
DOI: 10.1111/hel.12789
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori in familial mediterranean fever: A series of 120 patients from literature and from france”

Abstract: Introduction Familial Mediterranean Fever (FMF), the most common monogenic auto‐inflammatory disease, is characterized by recurrent febrile abdominal pain. Helicobacter pylori infection (HPI), one of the most frequent infections worldwide, can mimic an FMF attack. Objectives Identify FMF patients with HPI in a cohort of French FMF patients and the literature and identify features allowing to distinguish HPI from an FMF attack. Methods A retrospective study of all HPI cases was performed on the cohort of FMF pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Detecting elevation in CRP value in FMF patients with Hp infection correlates with Özaltin et al’s study 22 . A study concluded that Hp positivity could cause symptoms that could explain the inefficacy of colchicine in patients with a diagnosis of FMF and high CRP values 23 . In the literature, it was reported that there is basal inflammation in the non-attack period in patients with a diagnosis of FMF 4,6,19,20 .…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Detecting elevation in CRP value in FMF patients with Hp infection correlates with Özaltin et al’s study 22 . A study concluded that Hp positivity could cause symptoms that could explain the inefficacy of colchicine in patients with a diagnosis of FMF and high CRP values 23 . In the literature, it was reported that there is basal inflammation in the non-attack period in patients with a diagnosis of FMF 4,6,19,20 .…”
Section: Discussionmentioning
confidence: 68%
“…22 A study concluded that Hp positivity could cause symptoms that could explain the inefficacy of colchicine in patients with a diagnosis of FMF and high CRP values. 23 In the literature, it was reported that there is basal inflammation in the nonattack period in patients with a diagnosis of FMF. 4,6,19,20 Observing higher CRP and hs-CRP values in patients with FMF in our study supports this state.…”
Section: Discussionmentioning
confidence: 99%